(untitled) (ENTHYMEMA, 2019)
This study starts form the idea of how to stranslate what is commoned considered untranstaltable for modesty; the narrative motif of Putifarre’s wife, taken from Bible, has been variously employed in Middle Age literary texts and it was taken from The Book of Sindbad, which has benne so widespread translated in the West.